2015
DOI: 10.1016/j.trivac.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

ISCOM-based equine influenza vaccine: Duration of immunity and randomised clinical trials to assess an accelerated schedule of immunisation and efficacy

Abstract: a b s t r a c tThe widespread use of equine influenza (EI) vaccines plays an important role in the prevention and control of EI outbreaks. Vaccine strain updates, optimisation of immunisation schedules, and frequent evaluation of vaccine efficacy are necessary to maintain an acceptable level of protection and overall disease control. Results from three independent vaccine studies are reported here.Study 1: duration of immunity (exploratory research). The antibody and interferon (IFN) gamma response induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…All of the vaccinates had detectable but low SRH antibody titres at the time of experimental infection. The clinical protection demonstrated in the present study was similar to what has been observed for other EI vaccines when tested much sooner after immunisation, such as at the onset of immunity [ 12 , 25 , 32 , 42 , 43 ] or 2.5 months after V2 [ 14 ]. Virus shedding was measured after individual challenge by nebulisation in the present study, but the overall duration was significantly reduced in the vaccinates compared to the unvaccinated control ponies.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…All of the vaccinates had detectable but low SRH antibody titres at the time of experimental infection. The clinical protection demonstrated in the present study was similar to what has been observed for other EI vaccines when tested much sooner after immunisation, such as at the onset of immunity [ 12 , 25 , 32 , 42 , 43 ] or 2.5 months after V2 [ 14 ]. Virus shedding was measured after individual challenge by nebulisation in the present study, but the overall duration was significantly reduced in the vaccinates compared to the unvaccinated control ponies.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the significant time between V2 and the experimental infection (i.e., 158 days), the clinical outcome measured in the vaccinated group in the present study was similar to the outcome measured in ponies vaccinated with (1) an EI vaccine based on a canarypox-vectored vaccine expressing the haemagglutinin gene of EIV and experimentally infected with EIV 14 days after the second immunisation [ 35 ] and (2) a whole inactivated EI vaccine as well as experimental infection with EIV 14 or 15 days after V2 [ 12 , 26 ]. The clinical protection achieved in the current study was also similar or superior to the one recorded in ponies vaccinated with an ISCOM-based EI vaccine and experimentally infected with EIV 14 days [ 25 ] or 78 days after V2 [ 14 ], respectively.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations